Plants and butterflies of a small urban preserve in the Central Valley of Costa Rica - Nishida, Kenji (2009)
Costa Rica’s most populated area, the Central Valley, has lost much of its natural habitat, and the little that remains has been altered to varying degrees. Yet few studies have been conducted to assess the need for conservation in this area. We present preliminary inventories of plants, butterflies, and day-flying moths of the Reserva Ecológica Leonelo Oviedo (RELO), a small Premontane Moist Forest preserve within the University of Costa Rica campus, located in the urbanized part of the Valley. Butterflies are one of the best bio-indicators of a habitat’s health, because they are highly sensitive to environmental changes and are tightly linked to the local flora. A description of the RELO’s physical features and its history is also presented with illustrations. Approximately 432 species of ca. 334 genera in 113 families of plants were identified. However, only 57 % of them represent species native to the Premontane Moist Forest of the region; the rest are either exotic or species introduced mostly from lowland. More than 200 species of butterflies in six families, including Hesperiidae, have been recorded.